Correlation of MMP-2, TIMP-1, β2-MG and hs-CRP with the progression of retinopathy in patients with type 2 diabetes: Correlation of MMP-2, TIMP-1, β2-MG and hs-CRP with T2DM - Shi, Xiaobo; Yang, Min; Jiang, Xuguang; Li, Yanlong; Meng, Li (Cellular and Molecular Biology, 2023)
This study aimed to investigate the relationship between MMP-2, TIMP-1, β2-MG, hs-CRP and the progression of type 2 diabetic retinopathy (T2DM). For this purpose, 68 patients with T2DM retinopathy treated in our hospital were selected as the retinopathy group (REG), and 68 T2DM patients without retinopathy were selected as the control group (CDG). The serum levels of MMP-2, TIMP-1, β2-MG and hs-CRP were compared between the two groups. According to the international clinical classification of T2DM non-retinopathy (NDR), the patients were divided into non-proliferative T2DM retinopathy group (NPDR) (n=28) and proliferative T2DM retinopathy group (PDR) (n=40). The levels of MMP-2, TIMP-1, β2-MG and hs-CRP in patients with different conditions were compared. In addition, the Spearman method was used to analyze the correlation between the levels of MMP-2, TIMP-1, β2-MG, hs-CRP and glucose and lipid metabolism and the course of disease in patients with T2DM retinopathy (DR). Logistic multiple regression was used to analyze the risk factors of DR. Results showed that the levels of serum MMP-2, β2-MG and hs-CRP in PDR groups were raised than those in NPDR and NDR, while the serum TIMP-1 level was reduced. The levels of MMP-2, β2-MG and hs-CRP were positively correlated with the levels of HbA1c, TG and the course of disease in DR patients, while the levels of TIMP-1 in DR patients were negatively correlated with the levels of HbA1c, TG and the course of disease. The results of multivariate Logistic regression model showed that MMP-2, β2-MG and hs-CRP were independent risk factors for DR, and TIMP-1 was the protective factor for DR. In conclusion, the changes of peripheral blood MMP-2, TIMP-1, hs-CRP and β2-MG levels are closely related to the progression of T2DM retinopathy.